PENGARUH BUDAYA, SOSIAL, PRIBADI DAN MOTIVASI TERHADAP PERSEPSI KONSUMSI PANGAN POKOK NON BERAS MASYARAKAT DI KOTA DEPOK - Ahmad Jazilil Mustopa; Edmon Daris; Elpawati Elpawati (Syarif Hidayatullah State Islamic University Jakarta, 2017)
The successes of development within an agricultural sector in a country should be reflected by the ability of food self-sufficiency, at least in the food security. Currently, the food security is not considerably sufficient to represent the identity of an agricultural country. Yet, the government also have difficulties to reach the target of food self-sufficiencies until they finally make some policies to achieve the aim. One of the policies is a food diversification program reflected in the Presidential Regulation of Indonesia No. 22 in 2009 that regulatesfood consumption diversification acceleration policy based on local resources. It is prepared to reduce the problems that appear recently because most of Indonesian use rice as their staple foods. Meanwhile, the rice production is unbalanced if compared with the level of consumer demands. In fact, if it is considered in terms of fulfillment, in addition to rice, there are still a lot of staple foods that can be developed. The aims of this research are: 1) Identifying the characteristics of respondents in Depok city. 2) Analyzing the influences of the cultural, social, personal, and motivation variables to the perception of non-rice food consumption societies in Depok city. 3). Analyzing the influences of the cultural, social, personal, and motivation variables simultaneously to the perception of non-rice food consumption societies in Depok city.